Implementation of madrasah principal's strategy in developing teacher performance through academic supervision at state islamic junior high school 1 pontianak - Rudiansyah; Ahmad Yani T; Afandi; Agung Hartoyo; Dewi Novita (At Turots: Jurnal Pendidikan Islam, 2026)
The implementation of academic supervision by the madrasah principal is still insufficient to support teacher performance development. Innovative strategies are needed to boost sustainable teacher performance. This study aims to examine the implementation of the madrasah principal's strategy in developing teacher performance through academic supervision at Madrasah Tsanawiyah Negeri 1 Pontianak. Using a qualitative case study approach, data were collected through direct communication (interviews), observation, and document study. Data analysis went through the stages of data collection, data condensation, data presentation, and conclusion drawing (verification). Meanwhile, for data validity, member checks were used along with triangulation of sources, time, and methods/techniques. The results of the study indicate that the division of roles as strategy implementation between supervisors, madrasah principals, vice principals, and senior teachers forms a tiered supervision pattern. Where each supervisory team supervises junior teachers within the scope of related subject groups. So that the results of supervision obtained an increase in teacher performance with an average of 93 with the criteria of "very good." Keywords:strategy, madrasah principal, guidance, teacher performance, academic supervision